By the shores of Silver Lake - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperTrophy, 1971)
Ma and the girls follow Pa west by train where they make their home at a rough railroad camp and plan for their own homestead.
Newbery Honor Book, 1940.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Frontier and pioneer life -- South Dakota -- Fiction; Families -- South Dakota -- Fiction; South Dakota -- Fiction